Regulation and Function of ILC3s in Pulmonary Infections - Hoffmann, Joseph P.; Kolls, Jay K.; McCombs, Janet E. (Frontiers in Immunology, 2021)
Lower respiratory infections are among the leading causes of morbidity and mortality worldwide. These potentially deadly infections are further exacerbated due to the growing incidence of antimicrobial resistance. To combat these infections there is a need to better understand immune mechanisms that promote microbial clearance. This need in the context of lung infections has been further heightened with the emergence of SARS-CoV-2. Group 3 innate lymphoid cells (ILC3s) are a recently discovered tissue resident innate immune cell found at mucosal sites that respond rapidly in the event of an infection. ILC3s have clear roles in regulating mucosal immunity and tissue homeostasis in the intestine, though the immunological functions in lungs remain unclear. It has been demonstrated in both viral and bacterial pneumonia that stimulated ILC3s secrete the cytokines IL-17 and IL-22 to promote both microbial clearance as well as tissue repair. In this review, we will evaluate regulation of ILC3s during inflammation and discuss recent studies that examine ILC3 function in the context of both bacterial and viral pulmonary infections.